Nano-functionalization of textiles for superhydrophobicity and UV blocking - Lee, Qin Min. (2012)
Having water repellency and ultraviolet (UV) protection are one of the few important properties that is necessary in the fabrication of textiles. In this report, cotton fabrics were treated with CeO2 sol to fabricate surface roughness so as to enhance superhydrophobicity. The methodology of synthesizing and depositing CeO2 sol on textiles will be carried out through a sol-gel chemistry. The treated cotton sample will be characterized by scanning electron microscopy (SEM), Energy dispersive X ray spectroscopy (EDX), X-ray diffraction (XRD), water contact angle (WCA) measurement, and UV-vis spectrophotometry. The modified cotton surface not only displayed robust superhydrophobicity with a contact angle of 101.38°, but it also shows excellent protection against UV radiation after the infiltration of the CeO2 nanoparticles on the pristine cotton. Lastly, the degree of wetting behavior can be predicted using the two known models known as the Wenzel state and Cassie-Baxter State.